Realization of Three-Phase Voltage Source Inverter Controller Using Arm Cortex-M3 - Muhamad Aiman, Muhamad Azmi; Hamdan, Daniyal; Mohd. Shafie, Bakar (UM Power Energy Dedicated Advanced Centre (UMPEDAC), 2014)
Most of the renewable energy systems require an inverter that converts direct current (DC) to alternating current (AC) as a power supply. A lot of efforts has been made to achieve an inverter with high performance and high efficiency with low cost. This paper discusses the usage of renowned ARM Cortex-M3 processor in Arduino DUE as a controller for three phase voltage source inverter (VSI). The processor produces pure sinusoidal pulse width modulation (SPWM) in minimal computational power.